Behaviour of the tree-bush diversity in grazing zones in a natural protected area of the poblano dry tropic - García-Fragoso, Ana Laura; Guerrero-Rodríguez, Juan de Dios; Ortiz-Torres, Enrique; Rosas-Rosas, Octavio César; Quero-Carrillo, Adrián Raymundo; Rosas-Rosas, Octavio César (Ecosistemas y Recursos Agropecuarios, 2021)
The tropical dry forest is characterized by its high diversity and biological richness, which provides several environmental services; nonetheless, in recent years, some uncontrolled human activities contribute to its degradation and loss. This is an ecosystem of the Sierra del Tentzo State Reserve, in the State of Puebla, México, where the use of natural resources is the main source of income and livelihood of its inhabitants. Since there is controversy about the effect of grazing, the present study was proposed, whose objective was to determine the diversity of arboreal species in areas with and without grazing. A sampling of trees and shrubs with a height greater than or equal to one meter was carried out in the municipalities of Huehuetlán El Grande and Huaquechula, establishing 300 quadrants for each zone, where samples of each species were taken. Using the non-parametric estimator Chao 2 and the Shannon-Wiener (H ') was determined: diversity, dominance and equity, while species richness was obtained with accumulation curves. The values of H ' for the areas with and without grazing were high, but many of the species reported are of secondary succession, an indicative of disturbance, showing that grazing and the activities carried out there are having an important impact on the structure and functionality of the native arboreal-shrub diversity.